Dietary patterns and risk of obesity and early childhood caries in Australian toddlers: Findings from an australian cohort study - Bell, L.K.; Schammer, C.; Devenish, Gemma; Ha, D.; Thomson, M.W.; Spencer, J.A.; Do, L.G.; Scott, Jane; Golley, R.K. (MDPI, 2019)
We examined associations between dietary patterns at 12 months, characterised using multiple methodologies, and risk of obesity and early childhood caries (ECC) at 24–36 months. Participants were Australian toddlers (n = 1170) from the Study of Mothers’ and Infants’ Life Events affecting oral health (SMILE) birth cohort. Principal Components Analysis (PCA) and the Dietary Guideline Index for Children and Adolescents (DGI-CA) were applied to dietary intake data (1, 2 or 3-days) at 12 months, and regression analysis used to examine associations of dietary patterns with body mass index Z-score and presence of ECC at 24–36 months. Two dietary patterns were extracted using PCA: family diet and cow’s milk and discretionary combination. The mean DGI-CA score was 56 ± 13 (out of a possible 100). No statistically significant or clinically meaningful associations were found between dietary pattern or DGI-CA scores, and BMI Z-scores or ECC (n = 680). Higher cow’s milk and discretionary combination pattern scores were associated with higher energy and free sugars intakes, and higher family diet pattern scores and DGI-CA scores with lower free sugars intakes. The association between dietary patterns and intermediate outcomes of free sugars and energy intakes suggests that obesity and/or ECC may not yet have manifested, and thus longitudinal investigation beyond two years of age is warranted.